The Influence of Different γ-Irradiation Patterns on Factors that May Affect Cell Cycle Progression in Male Rats - Manal R. Mohammed; Azza M. El-Bahkery; Shereen M. Shedid (SAGE Publishing, 2022)
Most studies of the biological effects of ionizing radiation have been done on a single acute dose, while clinically and environmentally exposures occur under chronic/repetitive conditions. It is important to study effects of different patterns of ionizing radiation. In this study, a rat model was used to compare the effects of repetitive and acute exposure. Groups: (I) control, (II, III) were exposed to fractionated doses (1.5 GyX4) and (2 GyX4), respectively/24h interval, and (IV, V) were exposed to 6 Gy and 8 Gy of whole-body gamma irradiation, respectively. The gene expression of MAPT and tau phosphorylation increased in all irradiated groups but the gene expression of PKN not affected. TGFβ% increased at dose of 2 GyX4 only. In addition, the cell cycle was arrested in S phase. Micronucleus (MN) increased and cell proliferation decreased. In conclusion, the dose and pattern of ionizing radiation do not affect the MAPT and PKN gene expression, but TGF-β, p-tau, MN assay and cell proliferation are significantly affected. The dose of 2 GyX4 showed distinctive effect. Repetitive exposure may increase TGF-β%, which causes radio-resistance and, G2/M delay. Thus, the cell cycle could be regulated in a different manner according to the dose and pattern of irradiation.